Active learning a practical guide for college faculty - Weimer, Maryellen 1947- (Magna Publications, 2017)
Active Learning: A practical Guide for College Faculty offers everyday guidance for implementing and improving active learning in the college classroom. This collection of articles is appropriate for both the complete novice as well as the instructor who may have used active learning techniques before.